2021
DOI: 10.1016/j.bja.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygenation or standard oxygenation for gastrointestinal endoscopy with sedation in patients at risk of hypoxaemia: a multicentre randomised controlled trial (ODEPHI trial)

Abstract: Background: We aimed to determine whether high-flow nasal oxygen could reduce the incidence of decreased peripheral oxygen saturation (SpO 2 ) compared with standard oxygen in patients at risk of hypoxaemia undergoing gastrointestinal endoscopy under deep sedation. Methods: This was a multicentre, randomised controlled trial with blinded assessment of the primary outcome evaluating high-flow nasal oxygen (gas flow 70 L min À1 , inspired oxygen fraction 0.50) or standard oxygen delivered via nasal cannula or fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 34 publications
1
132
2
1
Order By: Relevance
“…Another important difference is that in our study, the initial oxygen flow in nasal mask and nasal cannula group was 4 L/min, while in Nay et al 14 study, the oxygen flow was 70 L/min in the HFNC group and 8 L/min in the standard nasal cannula group. These differences could have reduced the incidence of hypoxemia in the Nay et al 14 study compared with ours. However, a disposable HFNC oxygen circuit costs much more than a nasal cannula.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Another important difference is that in our study, the initial oxygen flow in nasal mask and nasal cannula group was 4 L/min, while in Nay et al 14 study, the oxygen flow was 70 L/min in the HFNC group and 8 L/min in the standard nasal cannula group. These differences could have reduced the incidence of hypoxemia in the Nay et al 14 study compared with ours. However, a disposable HFNC oxygen circuit costs much more than a nasal cannula.…”
Section: Discussioncontrasting
confidence: 69%
“…They found that HFNC oxygenation significantly reduced the incidence of hypoxemia from 22.9% to 5.8% and decreased frequent need for maneuvers to maintain free upper airways (11.1% vs 32.4%) and for increasing oxygen flow (7.9% vs 23.4%). 14 Our study differs from the Nay et al 14 study in that we only enrolled patients having gastroscopy. Another important difference is that in our study, the initial oxygen flow in nasal mask and nasal cannula group was 4 L/min, while in Nay et al 14 study, the oxygen flow was 70 L/min in the HFNC group and 8 L/min in the standard nasal cannula group.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Girişimler başlamadan önce ve sonrasında HFNC kullanmak desaturasyonu önleyebilir ya da uygulamayı yapan hekime zaman kazandırabilir. Endoskopide (41) ve bronkoskopide (42) HFNC kullanımı ile desatürasyonun azaldığı gösterilmiştir.…”
Section: İnvaziv Girişimlerunclassified